John Wick. Chapter 4 [videorecording (DVD)] - Hatten, Shay; Finch, Michael (Screenwriter); Reeves, Keanu; Yen, Donnie, 1963-; Skarsgård, Bill; Fishburne, Laurence, III, 1961-; Sanada, Hiroyuki, 1960-; Anderson, Shamier; Reddick, Lance; Sawayama, Rina, 1990-; Adkins, Scott, 1976-; Brown, Clancy; et al. (Lionsgate, 2023)
John Wick uncovers a trail to defeating The High Table. But before he can earn his freedom, Wick must face off against a new enemy with powerful associations across the globe and forces that turn old friends into foes.